2013
DOI: 10.1002/jssc.201300294
|View full text |Cite
|
Sign up to set email alerts
|

Separation and characterization of sucrose esters from Oriental tobacco leaves using accelerated solvent extraction followed by SPE coupled to HPLC with ion‐trap MS detection

Abstract: Sucrose esters (SEs) were successfully extracted from Oriental tobacco leaves using a new methodology based on accelerated solvent extraction followed by hydrophilic-lipophilic balanced cartridge cleanup step. The SEs were detected by HPLC with ion-trap MS detection using an electrospray interface operated in the positive ion mode. This methodology combines the high efficiency of extraction provided by a pressurized fluid and the highly sensitive characterization offered by ion-trap MS. Under the optimized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Acetonitrile, dichloromethane and ethyl acetate were commonly chosen for extraction of SEs from tobacco. 10,12,24 Herein, the extraction efficiency of three kinds of solvent was first investigated. The average values of peak areas obtained for five groups of sucrose esters from three replicates were used to evaluate extraction efficiencies.…”
Section: Optimization Of Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetonitrile, dichloromethane and ethyl acetate were commonly chosen for extraction of SEs from tobacco. 10,12,24 Herein, the extraction efficiency of three kinds of solvent was first investigated. The average values of peak areas obtained for five groups of sucrose esters from three replicates were used to evaluate extraction efficiencies.…”
Section: Optimization Of Sample Preparationmentioning
confidence: 99%
“…[6][7][8][9] There are already several reports on the separation and analysis of sucrose esters in tobacco. [10][11][12] The first method devised for the analysis of sugar esters was proposed by Severson et al 11 They integrated silylation and gas chromatography together to analyze the surface extracts of tobacco leaf. However, the method still required a long sample preparation period for clean-up of the sample, which led to introduction of contamination and sample loss.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported on the volatile components of tobacco. Conventional extraction methods, such as steam distillation , simultaneous distillation extraction , and solvent extraction have been used for the determination of volatile components in tobacco. However, these techniques are time‐consuming, result low extracting efficiency, involve toxic solvent, and even lead to the degradation of thermolabile compounds and potential hydrolysis reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites in it differ greatly in chemical properties and concentrations, which makes it a big challenge for component investigation . Most studies of tobacco are focused on targeted analysis to a specific class of metabolites, such as sucrose esters , glycosides , and amino acids , which risks losing important unknown information.…”
Section: Introductionmentioning
confidence: 99%